Stronger arms & upper body - Wuebben, Joe; Stoppani, James 1968- (Human Kinetics, 2009)
"Targeting shoulders, arms, upper back, chest, and abdominals, Stronger Arms & Upper Body features over 100 exercises for serious lifters, including specific instructions for mastering technique and advanced exercise variations to help lifters push past plateaus. Along with 33 programs and ready-to-use workout plans, detailed anatomical illustrations, explanations and variations for equipment needs, and the latest in advanced training methods, Stronger Arms & Upper Body provides the comprehensive, hard-core instruction you need for the results you want."--Jacket